Advances in attractive therapeutic approach for macrophage activation syndrome in COVID-19 - Chen, Shunyao; Zhang, Cong; Chen, Deng; Dong, Liming; Chang, Teding; Tang, Zhao-Hui (Frontiers in Immunology, 2023)
Nowadays, people have relaxed their vigilance against COVID-19 due to its declining infection numbers and attenuated virulence. However, COVID-19 still needs to be concern due to its emerging variants, the relaxation of restrictions as well as breakthrough infections. During the period of the COVID-19 infection, the imbalanced and hyper-responsive immune system plays a critical role in its pathogenesis. Macrophage Activation Syndrome (MAS) is a fatal complication of immune system disease, which is caused by the excessive activation and proliferation of macrophages and cytotoxic T cells (CTL). COVID-19-related hyperinflammation shares common clinical features with the above MAS symptoms, such as hypercytokinemia, hyperferritinemia, and coagulopathy. In MAS, immune exhaustion or defective anti-viral responses leads to the inadequate cytolytic capacity of CTL which contributes to prolonged interaction between CTL, APCs and macrophages. It is possible that the same process also occurred in COVID-19 patients, and further led to a cytokine storm confined to the lungs. It is associated with the poor prognosis of severe patients such as multiple organ failure and even death. The main difference of cytokine storm is that in COVID-19 pneumonia is mainly the specific damage of the lung, while in MAS is easy to develop into a systemic. The attractive therapeutic approach to prevent MAS in COVID-19 mainly includes antiviral, antibiotics, convalescent plasma (CP) therapy and hemadsorption, extensive immunosuppressive agents, and cytokine-targeted therapies. Here, we discuss the role of the therapeutic approaches mentioned above in the two diseases. And we found that the treatment effect of the same therapeutic approach is different.